(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Chronic generalized periodontitis is a prevalent inflammatory disease affecting the supporting structures of the teeth, leading to progressive alveolar bone loss and eventual tooth loss. Beyond local oral manifestations, increasing evidence indicates a strong association between periodontitis and systemic health conditions, including cardiovascular diseases, diabetes mellitus, respiratory disorders, and adverse pregnancy outcomes. This article provides a comprehensive review of the pathophysiological mechanisms linking chronic generalized periodontitis with systemic complications, highlighting the importance of early diagnosis, preventive strategies, and interdisciplinary management to improve both oral and overall health outcomes.